The Apalachicola Barrier Island complex: a benchmark for MIS 5e (125 ka) sea-level oscillations? - Nikos Georgiou; Alexander R. Simms; Roger C. Creel; Silas Dean; Denovan Chauveau; Ciro Cerrone; Claudia Caporizzo; Alessio Rovere (Geomorphology, 2026)

Splicing regulation by RS2Z36 controls ovary patterning and fruit growth in tomato - Stavros Vraggalas; Remus R. E. Rosenkranz; Mario Keller; Yolanda Pérez-Pérez; Samia Bachiri; Kerstin J. Zehl; Jessica Bold; Stefan Simm; Arindam Ghatak; Wolfram Weckwerth; Leila Afjehi-Sadat; Palak Chaturvedi; et al. (Plant Molecular Biology, 2026)
Fruit growth is mediated by cell division and expansion. In tomato, the model for fleshy fruit development, both processes are tightly linked to changes in gene expression, including transcriptional regulation and RNA processing. While several transcription factors are implicated in fruit developmental programs, the role of splicing regulators remains largely unexplored. Expression profiling of splicing-related genes revealed expression patterns. The serine/arginine-rich splicing factor RS2Z36 is expressed in ovaries and during early fruit development. Loss-of-function mutations in RS2Z36 result in ovaries with altered patterning and in smaller, ellipsoid fruits. rs2z36 mutants display elongated pericarp cells along the longitudinal axis of pre-anthesis ovaries, indicating that RS2Z36-dependent expansion patterns are established before anthesis. Based on RNA-seq analysis we identified 230 genes with altered splicing profile in ovaries of rs2z36.1 compared to WT and 235 differentially expressed genes. Proteome analysis further revealed several differentially abundant isoforms, including several cell wall proteins and modifiers that might be involved in ovary patterning and fruit growth. In addition, rs2z36-1 pericarps show increased deposition of LM6-recognized arabinan and AGP epitopes. Together, these findings identify RS2Z36 as a regulator of ovary and fruit development and highlight a previously underappreciated role for splicing control in shaping early fruit morphology.

From Ice to Isolation: A geochemical reconstruction of the palaeoenvironmental evolution of Gairloch, NW Scotland (UK), since the Last Glacial Maximum - Jennifer Taylor; David Selby; Jeremy M. Lloyd; Louise Best; Luca Podrecca; Bradley B. Sageman; Alexander R. Simms (Journal of Quaternary Science, 2026)
Complex relative sea‐level (RSL) changes are associated with the deglaciation of the British and Irish Ice Sheet (BIIS). Sediment archives from Loch Bad na h‐Achlaise, an isolation basin in NW Scotland, UK, span Late Glacial to Holocene time and record sea‐level change and ice proximity via a geochemical and biostratigraphic multiproxy approach. Osmium and carbon isotope, carbon and nitrogen content, and X‐ray fluorescence (XRF) data suggest that the basal sedimentary unit reflects a glaciomarine depositional setting, a finding previously unresolved due to an inadequate biostratigraphic framework. The 187 Os/ 188 Os record from the basin captures the RSL history of this site and illustrates the interplay between the local signal of glacial isostatic adjustment and the non‐local signal of glacio‐eustatic sea‐level rise. By coupling the 187 Os/ 188 Os data with a detailed age–depth model, our study demonstrates a period of RSL fall between 16.2 and 15.9 cal ka BP, which culminates in basin isolation. The close agreement between the biostratigraphy, where available, and the 187 Os/ 188 Os record confirms the viability of this isotope system as an RSL proxy not reliant on microfossil preservation and thus a potentially effective approach when poor microfossil preservation hampers palaeoenvironmental reconstruction.

New RSL constraints for the Minch from OSL-dated Lateglacial shorelines - Emily Huffman; Alexander R. Simms; Tom Bradwell; Louise Best; Jeremy M. Lloyd; Sarah L. Bradley; Regina DeWitt (Quaternary Science Reviews, 2025)

P30-11 Assessment of Disposable of e-vapour products using New Approach Methodologies shows marked reductions in toxicity relative to a cigarette - O. Komini; R. Derr; I. Brandsma; R. Wieczorek; S.J. Pour; E. Trelles-Sticken; C. Kasim; K. Papikinos; M. Stevenson; L. Simms (Toxicology Letters, 2025)

P30-06 Disposable E-Vapour Products Exhibit Lower in vitro toxicological Activity Than Cigarettes - M.A. Oltean; R. Wieczorek; S.J. Pour; E.T. Sticken; K. Papikinos; C. Kasim; O. Komini; M. Stevenson; L. Simms (Toxicology Letters, 2025)

P21-01 Assessment of a range of Next Generation Nicotine products using ToxTracker® and ToxProfiler™ MAX assays reveal marked reductions in biological activity compared to a cigarette - M. Stevenson; I. Brandsma; M. Meijer; M. Rijkers; B. ter Braak; L. Wolters; E. Trelles-Sticken; R. Wieczorek; S.J. Pour; T. Evenburg; F. Chapman; L. Simms (Toxicology Letters, 2025)

Reconstructing Late Pleistocene relative sea levels on transgressed shelves: an example from central California - Elisa Medri; Alexander R. Simms; Jared Kluesner; Samuel Y. Johnson; Stuart P. Nishenko; H. Gary Greene; James E. Conrad; Devin Rand (Quaternary Science Reviews, 2025)

Was Scotland covered by an ice sheet during Marine Isotope Stage 4? Insights from the pre‐Last Glacial Maximum marine terraces of northwest Scotland - Alexander R. Simms; Regina DeWitt; Sarah L. Bradley; Emily Huffman; Louise Best; Tom Bradwell; Jeremy M. Lloyd; Samuel B. Kachuck (Journal of Quaternary Science, 2025)
Raised shorelines provide important constraints on past sea levels, glacial isostatic adjustment (GIA), and rates and directions of vertical crustal motion. Although most raised shorelines across NW Scotland relate to post‐Last Glacial Maximum (LGM) glacial‐isostatic rebound, many undated shorelines lie above the marine limit established from isolation basins. Here, we present new optically stimulated luminescence (OSL) ages for a raised marine terrace at an elevation of 28 m in Slaggan Bay of NW Scotland. Four OSL ages suggest the feature is pre‐LGM, likely Marine Isotope Stage (MIS) 3. Global mean sea levels (GMSL) during MIS 3 are thought to have been ~40–60 m below present across most of the globe. We use a pair of GIA models to determine what ice sheet and sea‐level scenarios might provide an explanation for these anomalously high sea levels during MIS 3. Our results suggest that in the absence of tectonic activity, such high MIS 3 shorelines across NW Scotland require a MIS 4 ice sheet in Scotland, with postglacial rebound of the crustal depression following its demise during MIS 3 responsible for the elevated shoreline features at that time.

Insights into the sea-level history of the South Shetland Islands from ground penetrating radar on Livingston Island, Antarctica - Cameron Gernant; Alexander R. Simms; Regina DeWitt; Brittany Theilen; Christopher N. Garcia; Michael Goebel (Quaternary Science Reviews, 2025)

Beneficial death: A substantial element of evolution? - Patrick R. Winterhalter; Andreas Simm (Biogerontology, 2025)

Late Pleistocene sea-level constraints across Antarctica - Alexander R. Simms; Takeshige Ishiwa; Dominic A. Hodgson; Toru Tamura; Regina DeWitt (Quaternary Science Reviews, 2024)

P01-04 Extracts from different next generation product platforms show less potential to induce oxidative stress than extracts from cigarettes in human coronary artery endothelial cells (HCAECs) in vitro - E. Trelles Sticken; T. Evenburg; S.J. Pour; R. Wieczorek; M. Stevenson; L. Simms (Toxicology Letters, 2024)

Early Season Wheat Response to Electrochemically Precipitated Struvite in Various Soils in the Greenhouse - Tatum Simms; Kristofor R. Brye; Trenton L. Roberts; Lauren F. Greenlee (Journal of Soil Science and Plant Nutrition, 2024)
Fertilizer-phosphorus (P) materials can be recovered from wastewater and used to supplement mined phosphate rock, where one such material is struvite [MgNH 4 PO 4 ·6(H 2 O)]. This study aimed to compare electrochemically precipitated struvite (ECST) reclaimed from synthetic wastewater to other commercial fertilizer-P sources in cultivated soils from Arkansas [silty clay loam (AR-SiCL) and silt loam (AR-SiL)], Missouri [(silt loam; MO-SiL 1 and 2)], and Nebraska [silt loam (NE-SiL) and sandy loam (NE-SL)]. A greenhouse pot study was conducted for 60 days with unvernalized wheat ( Triticum aestivum ) using five fertilizer-P sources [ECST, chemically precipitated struvite (CPST), monoammonium phosphate (MAP), triple superphosphate (TSP), and an unamended control (UC)] to evaluate treatment effects on below (BG)- and aboveground (ABG) and total dry matter (DM) and tissue-N, -P, -K, -Ca, -Mg, and -Fe uptakes. The ECST treatment produced 44 g m −2 larger ABG-DM than CPST in the AR-SiCL, but 181 g m −2 larger than the UC in the MO-SiL 1. The ECST had similar or larger nutrient uptakes than CPST, MAP, TSP, and UC. Belowground-P, -N, and -Mg uptakes for ECST were generally similar for all soil-fertilizer-P source combinations, where ECST was 0.3 to 2.6 g m −2 larger than all other fertilizer-P sources. Plant property response from ECST was generally similar to or greater than CPST, MAP, TSP, and the UC across all soils. Results suggest that ECST is a prime candidate to be used as an effective, alternative fertilizer-P source, suitable for use in wheat production across multiple soil textures.

Constraining the radiocarbon reservoir age for the Southern Ocean using whale bones salvaged from early 20th century whaling stations - Claire Divola; Alexander R. Simms; Angela Sremba; C. Scott Baker; Ari Friedlaender; John Southon (Quaternary Science Reviews, 2024)

Emerging resilience metrics in an intensely managed ecological system - Nikolaos Toumasis; Daniel Simms; Will Rust; Jim Harris; John R. White; Joanna Zawadzka; Ron Corstanje (Ecological Engineering, 2024)

P22-16: Heated tobacco and e-vapour products induce lower biological activity compared to cigarettes using the ToxProfiler assay - O. Komini; B.T. Braak; L. Wolters; E.T. Sticken; R. Wieczorek; S.J. Pour; F. Chapman; L. Simms; M. Stevenson (Toxicology Letters, 2023)

P14-20: Chemical and biological assessment of a Heated Tobacco Product reveals marked reductions in aerosol toxicants and in vitro toxicity compared to a combustible cigarette - R.-D. Vasile; S.J. Pour; R. Wieczorek; E.T. Sticken; V. Troude; O. Dethloff; L. Mason; L. Simms; M. Stevenson (Toxicology Letters, 2023)

P14-13: Use of Quantitative In Vitro to In Vivo Extrapolation (QIVIVE) for the assessment of Non-Combustible Next Generation products - L. Simms; M. Moreau; E. Trelles Sticken; R. Wieczorek; S.J. Pour; F. Chapman; M. Stevenson (Toxicology Letters, 2023)

Population dynamics and life history of the endangered ciénega endemic Eryngium sparganophyllum in Arizona - Yue M. Li; Jeffery R. Simms; Theresa Condo; Dustin Wolkis; Ruixue Wang; Andrew Hatch; Elizabeth Makings; Steven Blackwell; Matthew Mayer (Journal of Arid Environments, 2023)

Subaqueous clinoforms created by sandy wave-supported gravity flows: Lessons from the Central California shelf - Elisa Medri; Alexander R. Simms; Jared Kluesner; Samuel Y. Johnson; Stuart P. Nishenko; H. Gary Greene; James E. Conrad (Marine Geology, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Local and regional constraints on relative sea‐level changes in southern Isle of Skye, Scotland, since the Last Glacial Maximum - Louise Best; Alexander R. Simms; Martin Brader; Jerry Lloyd; Juliet Sefton; Ian Shennan (Journal of Quaternary Science, 2022)
New relative sea‐level (RSL) data constrain the timing and magnitude of RSL changes in the southern Isle of Skye following the Last Glacial Maximum (LGM). We identify a marine limit at ~ 23 m OD, indicating RSL ~20 m above present c . 15.1 ka. Isolation basin data, supported by terrestrial and marine limiting dates, record an RSL fall to 11.59 m above present by c . 14.2 ka. This RSL fall occurs across the time of global Meltwater Pulse 1A, supporting recent research on the sources of ice melting. Our new data also help to resolve some of the chronological issues within the existing Isle of Skye RSL record and provide details of the sub‐Arctic marine environment associated with the transition into Devensian Lateglacial climate at c . 14.5 k cal a bp , and the timing of changes in response to the Loch Lomond Stadial climate. Glacio‐isostatic adjustment (GIA) model predictions of RSL deviate from the RSL constraints and reflect uncertainties in local and global ice models used within the GIA models. An empirical RSL curve provides a target for future research.

The long goodbye on a disappearing, ancestral island: a just retreat from Isle de Jean Charles - Jessica R. Z. Simms; Helen L. Waller; Chris Brunet; Pamela Jenkins (Journal of Environmental Studies and Sciences, 2021)

Current situations of animal data recording, dairy improvement infrastructure, human capacity and strategic issues affecting dairy production in sub-Saharan Africa - O. Opoola; R. Mrode; G. Banos; J. Ojango; C. Banga; G. Simm; M. G. G. Chagunda (Tropical Animal Health and Production, 2019)

Where do fish go when stranded on land? Terrestrial orientation of the mangrove rivulus Kryptolebias marmoratus - Noah R. Bressman; Mark Simms; Benjamin M. Perlman; Miriam A. Ashley‐Ross (Journal of Fish Biology, 2019)
The goal of the present study was to determine which sensory cues the mangrove rivulus Kryptolebias marmoratus , a quasi‐amphibious, hermaphroditic fish, uses to orient in an unfamiliar terrestrial environment. In a laboratory setting, K. marmoratus were placed on a terrestrial test arena and were provided the opportunity to move toward reflective surfaces, water, dark colours v . light colours, and orange colouration. Compared with hermaphrodites, males moved more often toward an orange section of the test arena, suggesting that the response may be associated with camouflage or male–male competition, since only males display orange colouration. Younger individuals also moved more often toward the orange quadrant than older individuals, suggesting age‐dependent orientation performance or behaviour. Sloped terrain also had a significant effect on orientation, with more movement downhill, suggesting the importance of the otolith‐vestibular system in terrestrial orientation of K. marmoratus . By understanding the orientation of extant amphibious fishes, we may be able to infer how sensory biology and behaviour might have evolved to facilitate invasion of land by amphibious vertebrates millions of years ago.

Social justice and mobility in coastal Louisiana, USA - Craig E. Colten; Jessica R. Z. Simms; Audrey A. Grismore; Scott A. Hemmerling (Regional Environmental Change, 2018)

Image segmentation for improved consistency in image-interpretation of opium poppy - Daniel M. Simms; Toby W. Waine; John C. Taylor; Timothy R. Brewer (International Journal of Remote Sensing, 2016)

Speleogenetic evidence from Ogof Draenen for a pre‐Devensian glaciation in the Brecon Beacons, South Wales, UK - ANDREW R. FARRANT; CHRISTOPHER J. M. SMITH; STEPHEN R. NOBLE; MICHAEL J. SIMMS; DAVID A. RICHARDS (Journal of Quaternary Science, 2014)
The British Isles have been affected by as many as 30 glaciations during the Quaternary. However, the evidence for pre‐Devensian glaciations in upland regions is scarce. Understanding the extent and timing of earlier upland glaciations is essential for modelling the long‐term evolution and sensitivity of the British Ice Sheet. Caves, being protected from surface erosion and weathering, can preserve evidence of earlier glaciations in the form of speleothem and sediment archives. The ∼70‐km‐long Ogof Draenen cave system in South Wales, UK, contains multiple cave levels related to changes in the surface topography and drainage during the past 0.5 Ma. The cave contains evidence of massive influxes of sediment that were sufficient to choke the cave and alter the underground drainage. Analysis of the cave sediments, passage morphology and geometry suggests the cave once acted as a subterranean glacial spill‐way before being overridden by ice. Speleothem U‐series data demonstrate that this sediment influx occurred before Marine Isotope State (MIS) 9, probably during the Anglian glaciation (MIS 12). Evidence from Ogof Draenen indicates the impact of subsequent glaciations on the landscape evolution of the region was minimal and that much of the surface topography dates from the Anglian. Copyright © 2014 British Geological Survey (NERC). Journal of Quaternary Science © 2014 John Wiley & Sons Ltd.

Towards improving the accuracy of opium yield estimates with remote sensing - Toby W. Waine; Daniel M. Simms; John C. Taylor; Graham R. Juniper (International Journal of Remote Sensing, 2014)

The application of time-series MODIS NDVI profiles for the acquisition of crop information across Afghanistan - Daniel M. Simms; Toby W. Waine; John C. Taylor; Graham R. Juniper (International Journal of Remote Sensing, 2014)

Genetic diversity and colony breeding structure in native and introduced ranges of the Formosan subterranean termite, Coptotermes formosanus - Claudia Husseneder; Dawn M. Simms; Jennifer R. Delatte; Changlu Wang; J. Kenneth Grace; Edward L. Vargo (Biological Invasions, 2012)

Fibroblast activation protein-α promotes tumor growth and invasion of breast cancer cells through non-enzymatic functions - Yan Huang; Avis E. Simms; Anna Mazur; Sophie Wang; Noel R. León; Barry Jones; Nazneen Aziz; Thomas Kelly (Clinical & Experimental Metastasis, 2011)

Characterization of cellulose production in Escherichia coli Nissle 1917 and its biological consequences - Cláudia Monteiro; Inder Saxena; Xiaoda Wang; Abdul Kader; Werner Bokranz; Roger Simm; David Nobles; Milan Chromek; Annelie Brauner; R. Malcolm Brown; Ute Römling (Environmental Microbiology, 2009)
Summary Bacterial species of the Enterobacteriaceae family produce cellulose and curli fimbriae as extracellular matrix components, and their synthesis is positively regulated by the transcriptional activator CsgD. In this group of bacteria, cellulose biosynthesis is commonly regulated by CsgD via the GGDEF domain protein AdrA, a diguanylate cyclase that produces cyclic‐diguanylic acid (c‐di‐GMP), an allosteric activator of cellulose synthase. In the probiotic Escherichia coli strain Nissle 1917 and its recent clonal isolates, CsgD activates the production of curli fimbriae at 28°C, but neither CsgD nor AdrA is required for the c‐di‐GMP‐dependent biosynthesis of cellulose at 28°C and 37°C. In these strains, the GGDEF domain protein YedQ, a diguanylate cyclase that activates cellulose biosynthesis in certain E. coli strains, is not required for cellulose biosynthesis and it has in fact evolved into a novel protein. Cellulose production in Nissle 1917 is required for adhesion of bacteria to the gastrointestinal epithelial cell line HT‐29, to the mouse epithelium in vivo , and for enhanced cytokine production. The role of cellulose in this strain is in contrast to the role of cellulose in the commensal strain E. coli TOB1. Consequently, the role of cellulose in bacterial–host interaction is dependent on the E. coli strain background.

Regulation of cytokine synthesis in cardiac surgery: Role of extracorporeal circuit and humoral mediators in vivo and in vitro - J. Börgermann; S. Flohé; R. J. Scheubel; O. Kuss; A. Simm; F. U. Schade; I. Friedrich (Inflammation Research, 2007)

Genetic diversity and genotypic differentiation between the sexes in swarm aggregations decrease inbreeding in the Formosan subterranean termite - C. Husseneder; D. M. Simms; D. R. Ring (Insectes Sociaux, 2006)

A BIOPSY SYSTEM FOR SMALL CETACEANS: DARTING SUCCESS AND WOUND HEALING IN TURSIOPS SPP. - Michael Krützen; Lynne M. Barré; Luciana M. Möller; Michael R. Heithaus; Colleen Simms; William B. Sherwin (Marine Mammal Science, 2002)
A bstract Together with PAXARMS (NZ), we developed a biopsy system for small cetaceans and tested it on four populations of bottlenose dolphins ( Tursiops spp.). The system consists of a modified 0.22 caliber rifle, and biopsy darts made out of polycarbonate with stainless steel biopsy tips. Animals were darted at a range of 2–15 m while travelling parallel to the vessel. Overall sampling success for obtaining biopsy samples when an animal was struck ranged from 96.6% to 100% in the four populations. However, hit rate varied for the four different populations. We did not observe a significant difference in strength of the reaction to the darting procedure when an animal was hit or missed, both among and within populations. Data from one population showed no significant difference in the reaction to biopsy sampling by four different age‐sex classes. The only factor that had a significant influence on darting success was the hit location. Furthermore, we observed a significant positive correlation between the size of the sample obtained and the reaction to biopsy sampling. Biopsy samples were sufficient for microsatellite and d‐loop analysis in 95.8% and for genetic sexing in 99% of all cases. In animals that we observed on a daily basis, wounds were healed after approximately 23 d.